(untitled) (Eurasian Scientific Herald, 2026)
This article highlights the importance of integrating physics and electrical engineering for developing professional competencies in engineering education. The article analyzes the main theoretical foundations of physics and its connections with electrical engineering. It describes the integration between physics and electrical engineering, the role of physical knowledge in developing engineers’ practical and analytical skills, as well as in effectively solving engineering problems